Model updating for undamped gyroscopic systems with connectivity constraints. Issue 5 (2nd September 2020) - Zhang, Hairui; Yuan, Yongxin
ABSTRACT: An important and difficult aspect for the finite element model updating problem is to make the updated model have physical meaning, that is, the connectivity of the original model should be preserved in the updated model. In many practical applications, the system matrices generated by discretization of a distributed parameter system with the finite element techniques are often very large and sparse and are of some special structures, such as symmetric and band structure (diagonal, tridiagonal, pentadiagonal, seven-diagonal, etc.). In this paper, the model updating problem for undamped gyroscopic systems with connectivity constraints is considered. The method proposed not only preserves the connectivity of the original model, but also can update the analytical matrices with different bandwidths, which can meet the needs of different structural dynamic model updating problems. Numerical results illustrate the efficiency of the proposed method.